The digital disruption of journalistic identity at the South African Broadcasting Corporation (SABC) - Oosthuizen, Nina-Celeste (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This research investigates changes in journalistic identity with the introduction of online journalism practices in the SABC newsrooms. The study is a qualitative analysis of in-depth interviews with 6 SABC journalists. It focuses on SABC journalists who embrace a professional identity. Participants were selected from all three of the SABC newsrooms: Television, Radio and Digital News. The research reveals that SABC News journalists are - due to digital production workflows - increasingly pressured to work on their own in the field, with additional responsibilities and fewer resources, while taking on editorial duties and managing corporate and personal social media accounts. As the roles of SABC journalists become digitally disrupted and blur with those of technicians, editors and marketers, I ask how this might in turn disrupt journalistic identity. The interviews reveal how these SABC journalists have always understood their identities and values in opposition to those of corporate SABC leadership. While they, the journalists, sometimes allowed editors to change their stories, this was not done without resistance; it was a strategic compromise, since they understood the greater balance of their work to serve the public. However, this notion of being separate from the corporate identity has been disrupted through digital and social media, as it conflates their identity with the SABC brand. Journalists experience this acutely through 'trolling'. Yet, conversely, some are also able to retain a sense of an independent professional identity through a direct relationship with the public on social media. Another key finding was that digital media disrupts the centrality of primary journalistic research or 'legwork', and instead, journalists increasingly spend time on the selection and repackaging of user-generated content. As some journalists are allocated more deskwork they experience a loss of status among their colleagues. The diminished role of journalists' primary research, or eye-witness testimony, has created tensions in journalistic identity and what it means to be a 'real' journalist. Despite their concerns for the danger of reporting in the field in South Africa, SABC journalists considered such verification work crucial to their identity and what it means to be a journalist.
Keywords: South African Broadcasting Corporation; Journalism Technological innovations -- South Africa; Digital media -- South Africa; Online journalism -- South Africa; Identity (Psychology) in mass media; Public broadcasting Political aspects -- South Africa; Journalistic ethics; Mass media Employees; Mass media Objectivity -- South Africa; Journalism Social aspects -- South Africa